Da'wah Generate The Art of Malay Heritage in Terengganu - Berhanundin, Abdullah; Badlihisham, Mohd Nasir; Ahmad Syukran, Baharuddin (2016)
Islamic Da’wah has grown in Terengganu began before the year 1303 AD missionary in extended periods of time, has managed to adopt Islamic values in Malay heritage. The purpose of writing this article is to detail the findings of research against some artistic practices that have been absorbed by Islamic art. This study uses text analysis method (content analysis) and documentation review and then processed in a descriptive writing. Analysis carried out on the facts of history and current information related to the practice of the arts in the community. The outcomes of this study verify that the application of Islamic values could change the Malay traditional arts heritage. Limitations of this study focuses on Malay language Jawi writing, learning the Quran, architecture, calligraphy, crafts and martial arts in the state of Terengganu. The impact of this study is able to enlighten the community that is very important to know the art heritage from the Islamic perspective and appreciate the art of Malay heritage.